2020
DOI: 10.15517/lank.v20i2.43358
|View full text |Cite
|
Sign up to set email alerts
|

Discoveries in indigenous territories: Two new species of Lepanthes (Orchidaceae: Pleurothallidinae) in southwestern Colombia

Abstract: Two new species of Lepanthes from the Central Cordillera of the Colombian Andes are described  and illustrated. Both were found during a botanical expedition to Puracé National Natural Park, within the  high Andean forests ecosystem of the municipality of Puracé, in the department of Cauca. Key Words: Cauca, Colombian Massif, Kokonukos, Paletará, Puracé National Natural Park

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Lepanthes nubiamuñozana is a new species that can be easily recognized by its lanceolate leaves and its racemose, loose, and long pendant inflorescences. It is probably related to the other racemose species: Lepanthes biloba Luer & R. Escobar, Lepanthes guanacasensis Luer & R. Escobar, Lepanthes kokonuko J. S. Moreno & Pisso-Florez, Lepanthes muscula Luer & R. Escobar and Lepanthes osiris Luer & R. Escobar (Luer and Thoerle, 2012; Moreno et al, 2020). But the most similar species is undoubtedly Lepanthes kokonuko (Fig.…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Lepanthes nubiamuñozana is a new species that can be easily recognized by its lanceolate leaves and its racemose, loose, and long pendant inflorescences. It is probably related to the other racemose species: Lepanthes biloba Luer & R. Escobar, Lepanthes guanacasensis Luer & R. Escobar, Lepanthes kokonuko J. S. Moreno & Pisso-Florez, Lepanthes muscula Luer & R. Escobar and Lepanthes osiris Luer & R. Escobar (Luer and Thoerle, 2012; Moreno et al, 2020). But the most similar species is undoubtedly Lepanthes kokonuko (Fig.…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
“…Lepanthes nubiamuñozana is a new species that can be easily recognized by its lanceolate leaves and its racemose, loose, and long pendant inflorescences. Escobar (Luer and Thoerle, 2012;Moreno et al, 2020). But the most similar species is undoubtedly Lepanthes kokonuko (Fig.…”
Section: Lepanthes Nidiagongoranamentioning
confidence: 99%
“…Nonetheless, taxonomic studies for Maxillaria remain scarce in both countries, and new species can still be found (Zambrano-Romero & Solano-Gómez 2016). Recent explorations conducted in the last few years in the Andes of southwestern Colombia and northern Ecuador expanded our knowledge of orchid diversity, notably in the poorly studied Puracé National Natural Park (PNNP), where two new species of orchids have been described in recent years (Moreno et al 2020). In the latest expeditions in Colombia and Ecuador, we found two populations of a morphologically distinctive species from the genus Maxillaria, which we propose here as a new species.…”
mentioning
confidence: 99%
“…The genus is exclusively neotropical, distributed from Mexico to Bolivia as well as the West Indies, but its center of distribution is in the high Andes, especially in Colombia and Ecuador, between 1500 and 3000 m of elevation in moist forests on mossy twigs or small branches (Luer & Thoerle 2012). With more than 300 species (Moreno et al 2020, Vieira-Uribe & Moreno 2019, Viveros et al 2015, Colombia is one of the countries with the highest diversity in Lepanthes species, with almost 68% of these being endemic (Viveros et al 2015).…”
mentioning
confidence: 99%